PENGARUH EARNING PER SHARE (EPS), DEBT TO EQUITY RATIO (DER) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2007-2011) - Murni Mussalamah, Arum Desmawati; Isa, Muzakar (Benefit, 2015)
The aim of this study is to test the effect of Earning Per Share (EPS), Debt to Equity Ratio (DER), and Return On Equity (ROE) to stock price. This study was chosen because there were still differences between one study and another. There was also distinct condition between theory and the reality.This study was conducted using secondary data. Samples were taken using purposive sampling technic. From one hundred and twenty manufacture company, sixty were chosen due to its complete financial report from 2007-2011. The analysis methods used for this study is double linier regression analysis.Using regression analysis,it was showed that Earning Per Share (EPS) had a positive and significant effect, Debt to Equity Ratio (DER) had a negative dan significant effect, meanwhile Return On Equity (ROE) had a positive and significant effect to stock price. Taken together, it was showed that 90,4% variation and stock price could be described by EPS, DER and ROE variable.The rest (9,6%) could be described by other variables outside the model.